2013
DOI: 10.1002/jbmr.2060
|View full text |Cite
|
Sign up to set email alerts
|

Changes of MicroRNA Profile and MicroRNA-mRNA Regulatory Network in Bones of Ovariectomized Mice

Abstract: Growing evidence shows the possibility of a role of microRNAs (miRNA) in regulating bone mass. We investigated the change of miRNAs and mRNA expression profiles in bone tissue in an ovariectomized mice model and evaluated the regulatory mechanism of bone mass mediated by miRNAs in an estrogen-deficiency state. Eight-week-old female C3H/HeJ mice underwent ovariectomy (OVX) or sham operation (Sham-op), and their femur and tibia were harvested to extract total bone RNAs after 4 weeks for microarray analysis. Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 53 publications
4
44
0
Order By: Relevance
“…MiRNAs -127, -133a, -133*a, -133b, -136, -206, -378, and -378* were upregulated after ovariectomy, whereas miR-204 was downregulated [96]. This study also demonstrated that miR-127 suppressed and miR-136 enhanced osteoblast differentiation, whereas both miRNAs promoted cell death in osteocytic cells.…”
Section: The Role Of Mirnas In Osteoblastsmentioning
confidence: 64%
“…MiRNAs -127, -133a, -133*a, -133b, -136, -206, -378, and -378* were upregulated after ovariectomy, whereas miR-204 was downregulated [96]. This study also demonstrated that miR-127 suppressed and miR-136 enhanced osteoblast differentiation, whereas both miRNAs promoted cell death in osteocytic cells.…”
Section: The Role Of Mirnas In Osteoblastsmentioning
confidence: 64%
“…8 miRNAs were identified (miR-127, −133a, −133a*, −133b, −136, −206, −378, −378*) upregulated but miR-204 was downregulated in OVX mice; they also confirmed that miR-127 and –136 as negative regulators for bone formation in UAMS-32 and MLO-Y4 cells in vitro [20]. Meanwhile, miR-21, miR-23a, miR-24, miR-25, miR-100 and miR-125b are upregulated in osteoporotic fracture patients in a clinical study [21].…”
Section: Mirnas Regulation During the Bone Remodelingmentioning
confidence: 95%
“…MicroRNAs (miRNAs) are evolutionarily conserved, small (~22 nucleotides), singlestranded non-coding RNAs that silence the expression of specific gene by base-pairing to the 3'-untranslated regions of target mRNAs on post-transcriptional level [3][4][5]. At present, numerous studies have indicated that miRNA was a crucial component in the development of osteoporosis [6][7][8][9][10][11]. For example, miR-34a blocks osteoporosis by inhibiting Tgif2 [12]; miRNA-148a regulates osteoclastogenesis via targeting MAFB [13]; and miRNA-142-3p induces cell death in osteoclasts depending on RANKL [14].…”
Section: Introductionmentioning
confidence: 99%